Conditional knockout of N-WASP enhanced the formation of keratinizing squamous cell carcinoma induced by KRasG12D - Kalailingam, Pazhanichamy (2024)
Squamous cell carcinoma (SCC) is one of the most common forms of skin cancer in humans, and Neural Wiskott-Aldrich Syndrome Protein (N-WASP) plays a crucial role in epidermal homeostasis. To elucidate the role of N-WASP in skin cancer, we generated mice which expressed constitutively active KRas (KRasG12D) in keratinocytes with either homozygous (N-WASPKOG12D) or heterozygous (N-WASPHetG12D) N-WASP knockout upon Tamoxifen (TAM) injection. Both the N-WASPKOG12D and N-WASPHetG12D mice had similar body weights and no congenital malformations prior to the injection of TAM. Within 2 weeks of the injections, the N-WASPKOG12D mice exhibited significant reductions in weight coupled with visible tumors at numerous sites, unlike the N-WASPHetG12D mice, which had no visible tumors. We found that both sets of mice had oily, sticky skin and wet eyes 3 weeks after their exposure to TAM, indicating the overproduction of sebum/meibum. At 37 days post TAM injection, several notable observations were made. Tumors collected from the N-WASPKOG12D mice had small- to large-sized keratin pearls that were not observed in the N-WASPHetG12D mice. A Western blot and immunostaining analysis both highlighted significantly higher levels of expression of SCC markers, such as the cytokeratins 8, 17, 18, and 19 and TP63, in the tumors of the N-WASPKOG12D mice compared to those of the latter group. Furthermore, we noted increases in the expression levels of EGFR, P-ERK, GLUT1, P-mTOR, and P-4EBP in the N-WASPKOG12D mice, suggesting that the deletion of N-WASP in the keratinocytes enhanced KRas signaling and glucose uptake, resulting in aggressive tumor formation. Interestingly, a thickening of the epidermal layer within the esophagus and tongue was only observed in the N-WASPKOG12D mice. Immunostaining for PCNA emphasized a significantly higher number of PCNA-positive cells in the skin of the N-WASPKOG12D mice compared to their counterparts, implying that epidermal thickening and enhanced tumorigenesis are due to an increased proliferation of keratinocytes. Through our results, we have established that N-WASP plays a tumor-suppressive role in skin cancer.